Developing Ethnomathematics Teaching Materials Using the Wooden Puppet Context Through a Culturally Responsive Teaching Approach - Siti Maryam Rohimah; Eka Firmansyah; Feby Inggriyani; Bunga Yasmin Oktapianti; Desi Anawati (Mathematics Education Journal, 2026)
This study aimed to develop ethnomathematics teaching materials using the wooden puppet context through a Culturally Responsive Teaching (CRT) to enhance elementary students’ numeracy literacy while integrating local cultural values in support of Sustainable Development Goal 4 (Quality Education). This study employed a Research and Development (R&D) method based on a multiphase design model involving 66 fifth-grade students from a public elementary school in Jelekong, West Java, Indonesia. The development process comprised needs analysis, teaching material development, expert validation, limited trials, revisions, and classroom implementation. Data were collected using numeracy literacy tests, classroom observations, questionnaires, interviews, and field notes. Qualitative data were analyzed through data reduction, data display, and conclusion drawing, while quantitative data were analyzed using the Shapiro–Wilk normality test, the Wilcoxon Signed-Rank Test, normalized gain, and effect size. The findings demonstrate that the developed teaching materials are valid, practical, and effective, resulting in a statistically significant improvement in students’ numeracy literacy, as indicated by a high normalized gain and a large effect size. These findings suggest that ethnomathematics teaching materials developed using the wooden puppet context through CRT enhance students’ numeracy literacy while promoting appreciation of Sundanese cultural heritage.